Sacrality in Modern Ukrainian Poetics: Metamorphoses of Values - Lazorevych, Iryna (Occasional papers on religion in Eastern Europe, 2021)
This is a study of the influence of religious sacrality on modern Ukrainian literature, particularly poetry, analyzing those sacred meanings that the current Ukrainian mentality actively uses. So far, it eclectically synthesizes the ideological impulses of traditional Christian religiosity (which even in the times of Communism retained its natural strength, especially in the Western regions of Ukraine), and elements of Soviet ideologemes and pragmatism of the modern transitional period. At the same time, it uses certain inclinations to new communication with sacred, which is felt by some of the important creators of modern Ukrainian culture. In this article, the author uses specific examples to demonstrate the manifestations of Christian sacredness, canonicity/noncanonicity in modern poetry and analyzes them, answering the question of the purpose for which the poet used a particular symbol. Also, the researcher created a survey for writers, which provided direct conclusions about what the poets themselves invest in their work as well as their vision of how religion influences Ukrainian writers in current and future poetic art forms. After all, the interpretation of creativity by unrelated scholars is not the same as their own words about the motives of their work. This is an element of novelty of the research, in which interdisciplinary approach combines religious, aesthetic, and literary aspects.